The female secondary stipend and assistance program in Bangladesh what did it accomplish?. - Khandker, Shahidur Rahman; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Are subsidies to female education worth supporting to enhance socioeconomic and demographic changes? In Bangladesh, how did FSSAP impact the education of children, and boys in particular? The paper also explores its impact on female labor force participation, as well as age at marriage, fertility, and other effects on society.
Keywords: Gender -- Health care -- Bangladesh; Education -- Economic aspects -- Bangladesh; Electronic book